The Impact of Negative Online Reviews by Social Media Influencers on the Formation of Brand Loyalty to Cosmetic Products - Hasrini Hasrini; Kussudyarsana Kussudyarsana; Edy Purwo Saputro (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates how negative electronic word-of-mouth (e-WOM) from social media influencers affects brand loyalty in the cosmetics industry. Specifically, it examines the mediating roles of brand attitude and consumer dissatisfaction and the moderating role of influencer credibility. Using a quantitative, associative design, data were gathered from 250 respondents who had been exposed to negative influencer reviews of cosmetic products through purposive sampling. A structured questionnaire was administered, and the data were analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The results reveal that negative influencer reviews significantly weaken brand attitude, which subsequently increases consumer dissatisfaction and reduces brand loyalty. Brand attitude and dissatisfaction significantly mediate the relationship between negative reviews and brand loyalty, indicating that unfavorable influencer content can indirectly drive brand disloyalty through these psychological pathways. However, influencer credibility does not significantly moderate the impact of negative reviews on brand attitude. These findings highlight the critical role of managing e-WOM and monitoring influencer content to protect brand equity. For cosmetic brands, proactive communication strategies and consumer engagement are essential to mitigate the adverse effects of negative influencer reviews. The study contributes to digital marketing literature by integrating mediation and moderation mechanisms into the understanding of how negative e-WOM shapes brand loyalty.